Prove that \(\displaystyle \prod _{ r=0 }^{ a } \binom{a}{r} =\left(\prod _{ r=0 }^{ b } \binom{b}{r} \right)\left(\prod _{ r=1 }^{ a-b }{ \frac { { (b+r) }^{ b+r-1 } }{ (b+r-1)! } }\right )\) , where \(a>b\).

Prove that \(\displaystyle \prod _{ r=0 }^{ a } \binom{a}{r} =\left(\prod _{ r=0 }^{ b } \binom{b}{r} \right)\left(\prod _{ r=1 }^{ a-b }{ \frac { { (b+r) }^{ b+r-1 } }{ (b+r-1)! } }\right )\) , where \(a>b\).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestCan I mention really quickly that in this problem, you didn't specify that the brackets meant the floor function? To avoid ambiguity, write \(\lfloor x\rfloor\) (code:

`\lfloor x\rfloor`

) instead of \([x]\). (P.S. How do you do a private message here?) – Akiva Weinberger · 2 years agoLog in to reply

– Abhishek Sharma · 2 years ago

My bad. I have corrected it now.Log in to reply